Diet-microbiome covariation across three giraffe species in a close-contact zone - Elin Videvall; Brian A. Gill; Michael B. Brown; Hannah K. Hoff; Bethan L. Littleford-Colquhoun; Peter Lokeny; Paul M. Musili; Tyler R. Kartzinel (Global Ecology and Conservation)
The biodiverse group of ruminant mammals are entirely dependent on their gut microbiota to extract energy and nutrients from their foods, making these symbionts vital to survival. Because variation in wildlife diets can select for distinct communities of gut bacteria, different foraging choices can have both nutritional effects and other microbially-mediated effects on animal well-being. Despite the proliferation of studies focusing on host-microbiome interactions in recent decades, few prior studies have quantified the level and extent of diet-microbiome linkages in wildlife. Therefore, we used DNA metabarcoding to compare the diets and gut microbiomes of giraffes, the world’s largest ruminant. We focused on three giraffe species—reticulated, northern, and Masai—that occur along a near-contact zone in equatorial Kenya. We found large differences in both the composition and diversity of diets and microbiomes within and among populations. However, contrary to expectations, we found very little evidence for links between the composition of individual diets and their corresponding microbiomes. Instead, geographic proximity strongly predicted diet similarity whereas host-species identity strongly predicted microbiome composition. The lack of diet-microbiome linkages across these giraffe populations—coupled with the evidence that species differed strongly in diet and microbiome compositions—highlights the possibility that their history of ecological and evolutionary divergence has generated unique, species-specific gut microbiomes. Moreover, striking levels of diet variation were revealed among neighboring populations of giraffe from the same species, and thus baseline knowledge of their resource-use diversity could support ongoing efforts to geographically tailor management strategies aimed at conserving local food staples under environmental change.